Phylogeny of Stromateiformes (Teleostei; Percomorphacea) based on phenotypic data - Pastana, Murilo Nogueira de Lima (2019)
The division Percomorphacea encompasses a major fraction of the extant fish diversity, including over half of all known ray-finned fishes and approximately one fourth of the living vertebrates. The interrelationships among the major percomorphacean lineages are still far from a satisfactory resolution. Among the 30 percomorphacean orders, Stromateiformes encloses 77 extant species distributed into 16 genera and six families - Amarsipidae, Ariommatidae, Centrolophidae, Nomeidae, Stromateidae, and Tetragonuridae. Members of this order are globally distributed in temperate and tropical oceans and exhibit two extraordinary morphological specializations: the presence of a pharyngeal sac and of a subdermal canal plexus over the head and trunk. The phyletic status of Stromateiformes has never been adequately tested on morphological grounds and the monophyly of the order has been recently rejected by multiple molecular analyses. Moreover, stromateiforms have been indecisively aligned with disparate percomorphacean taxa by both morphology- and molecular-based studies. The present work delved into these questions and presented a comprehensive phylogenetic revision of Stromateiformes based on an exhaustive analysis of 218 phenotypic characters and 66 terminal taxa encompassing all valid stromateiform genera, as well as all percomorphacean families somehow aligned with stromateiforms in prior studies. The resulting topology retrieves the order as monophyletic, supported by four unequivocal synapomorphies. Amarsipidae, the only stromateiform lacking a pharyngeal sac, is resolved as the sister group of the remaining members of the order. Centrolophidae is not monophyletic, with five of its genera grouped into a basal clade, whereas the other two appear as successive sister groups of a clade containing the remaining stromateiform families. All these families are recovered as monophyletic with the following cladistic arrangement: Nomeidae (Stromateidae (Tetragonuridae, Ariommatidae)). A clade composed by Bramidae and Caristiidae is herein hypothesized the sister group of stromateiforms, although this arrangement is supported by only a single unequivocal synapomorphy. The present study further hypothesizes that the remarkable symbiotic relationship between juvenile stromateiforms and gelatinous invertebrates (e.g. medusa and salps) is probably associated with the evolution of some of its most remarkable morphological specializations, such as the presence of dendritic pyloric caeca, subcutaneous canal plexuses, and the pharyngeal sac.